Characterization of dissolved organic matter in the rhizosphere of phytostabilizer Athyrium wardii (Hook.) involved in enhanced metal accumulation when exposed to Cd and Pb co-contamination. (November 2020) - Zhan, Juan; Huang, Huagang; Yu, Haiying; Zhang, Xizhou; Wang, Yongdong; Li, Tingxuan
Abstract: The characterization of DOM and its effect on heavy metal solubility in soils have been widely concerned, while few concerns on the phytostabilization of multi-metal contaminated soils. A pot experiment was performed to characterize dissolved organic matter (DOM) in the rhizosphere of the mining ecotype (ME) and non-mining ecotype (NME) of Athyrium wardii (Hook.) when exposed to Cd and Pb simultaneously, and investigate its effect on Cd and Pb solubility in soils. The ME presented more DOM in the rhizosphere when exposed to Cd and Pb simultaneously than that exposed to single Cd or Pb, and also than the NME. The acid fractions (hydrophilic acid, hydrophobic acid) and hydrophilic fractions (hydrophilic acid, hydrophilic neutral, and hydrophilic base) were the dominant parts of DOM in the ME rhizosphere. The ME presented more acid and hydrophilic fractions in the rhizosphere when exposed to Cd and Pb simultaneously. Meanwhile, there were more O–H, C–O, N–H and C–H, assigned to carboxylic groups, phenolic groups, hydroxyl groups, and/or amino groups, present in DOM from the rhizosphere of ME when exposed to Cd and Pb simultaneously. These results highlighted the acid characteristics of DOM in the rhizosphere of ME when exposed to Cd and Pb simultaneously. DOM in the rhizosphere of ME thereby showed greater complexation degree for Cd (68%) and Pb (77%), thus showing greater ability to enhance Cd and Pb solubility in soils when exposed to Cd and Pb simultaneously. This is thereby considered to be one of the key processes for enhancing Cd and Pb uptake by the ME when exposed to Cd and Pb simultaneously. Graphical abstract: Image 1 Highlights: ME showed more DOM in rhizosphere soils when exposed to Cd and Pb simultaneously. DOM in ME rhizosphere showed more O–H, N–H, C–O and C–H functional groups. DOM in ME rhizosphere showed more acid and hydrophilic fractions, thus greater ability to enhance Cd and Pb solubility. Thus, Cd and Pb uptake by ME enhanced when exposed to Cd and Pb simultaneously. Abstract : DOM in the rhizosphere of the ME shows greater ability to enhance Cd and Pb solubility in soils and promote Cd and Pb uptake by roots of the ME, thus showing great benefit to the phytostabilization of Cd and Pb co-contaminated soils by the ME.